Antibiotic Resistance A One-Health Approach - Martino, Piera Anna (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Antibiotic resistance represents one of the most important challenges in the world and involves humans, animals and the environment.For this reason, it is increasingly important to focus our attention on the present scenarios and the future prospects relating to this problem. The One Health approach helps us and can provide the tools to consider the problem from different points of view, also providing alternative solutions to the use of the antibiotic itself.